Analysis of Quality Success Factors for Road Pavement Layers in Road Construction Projects - Napitupulu, Roma Artha Uly; Putra, I Nyoman Dita Pahang; Widowati, Elok Dewi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Road construction projects are highly complex and therefore require effective project management. particularly in terms of quality control. to ensure that pavement performance remains optimal and meets standards. This study aims to evaluate quality compliance in construction projects. Quality evaluation must be conducted on a construction project to determine the project’s quality success rate. Quality evaluation must be conducted on a construction project to determine the project’s quality success rate. Quality evaluation is performed by analyzing the comparison of field test results with technical standard specifications. Among the evaluation parameters are the CBR value. density. and asphalt layer thickness. Additionally. an analysis of factors that can influence quality success in construction projects is required. The research results indicate that all quality parameters of the road pavement layers have met or even exceeded the established quality standards and were successfully implemented according to the plan with positive deviation values. Analysis of the factors influencing quality success based on the Relative Importance Index (RII) revealed that the most dominant factors are material conformity with technical specifications. material quality. pre-use material testing. and equipment productivity. with an RII value of 1.00 (High). Overall. the quality and success of the pavement layer in the construction project is influenced by optimal control over technical factors in the field. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry. Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 16: Peace. Justice. and Strong Institutions